PENGARUH DAYA TARIK WISATA TERHADAP MINAT KUNJUNGAN WISATAWAN DI SERULINGMAS INTERACTIC ZOO PADA SAAT DIKELOLA PIHAK BUMD - Siti Maesaroh; Isna Maulana Cahyaningrum (Medikonis, 2020)
ABSTRACT This research aims to determine the influence of tourist attraction partially and simultaneous to the interest of visitors the facilities, services, tourist destinations and event in Serulingmas Interactive Zoo. The method in this sampling is used the Slovin formula, data analysis methods used is multiple linear regression analyses, using the help of SPSS programmes. The test results of the hypothesis, indicating that the facility variable (X1) has a significant positive effect on the interest of visitors. The service variables (X2) have significant positive impact on the interest of visitors. The tourist destination variables (X3) is not significant to the interest of visitors. Event variables (X4) is not significant to the interest of visitors. Based on the results of the research can be partially inferred that there is a positive and significant relationship between facilities and the interest of visitors, there is a positive and significant relationship between the service and the interest of visitors, there is a positive and insignificant relationship between tourist destinations and the interest of visitors, there is a positive and insignificant relationship between events and the interest of visitors. Simultaneously all variables are influential and significant to the interest of visitors. This determination test (R ²) shows that a variable of visitors interest can be influenced by variable facilities, services, tourist destinations and events while the rest are influenced by other variables that are not filed in this research